ANALISA PENGARUH DISTORSI HARMONISA SAAT PENGOPERASIAN FILTER HYBRID TERHADAP UNJUK KERJA MOTOR INDUKSI 3 FASA - Kadek Ary Susiawan; I Wayan Rinas; I Made Suartika (Jurnal SPEKTRUM, 2021)
The increasing. use of non-linear loads can make. harmonic distortion in the current andvoltage waves so that it can reduce the. reliability and quality of the. power system. Non-linearloads that are often used are induction motors, consequently the use of induction. motors willhave an impact on the high harmonics. of the system. The impact. of these harmonics can bereduced by using a. hybrid filter. The method used is. direct measurement of the object understudy in the form. of current data, motor rotation and 3 induction motor THDi. This researchuses a Simulink-based simulation. which aims to reduce the. harmonic content in. the networkand to see the effect of harmonics. on the performance of the. 3-phase induction motor onrotation and torque. The. results of the. analysis show. that the hybrid filter. can. reduce theharmonic content in the network. The decrease that occurs in THDi is 11.96% in the R phase,11.95% in the S. phase and 11.96% in the T phase with a load of 3 motors. Using hybrid powerfilter is able to make the motor rotation stable at 0.17 s. However, the rotation. of the. inductionmotor remains at. 1498 rpm and a torque of 0.4682 Nm.